The Role of Public Spending Policies in Boosting GDP in Iraq - Ayad ALI Al-Tamimi*, Mamdooh; Hatem Alwan, Ghufran (Journal of Economics and Administrative Sciences, 2024)
Purpose: The research seeks to show the role of public spending policies in promoting GDP by stating the role of spending policy indicators in GDP during the research period.Theoretical Framework: The research deals with many concepts related to the subject of the study, which are public spending and its policies, in addition to concepts related to public expenditure policy indicators. Also, the definition of GDP and its trends in the Iraqi economy.Design/Methodology/Approach: Use the financial statements for the period (2004-2021) to knowing the trends of public spending in the Iraqi economy and to knowing the role played by analyzing the spending policies used by the government in directing public spending. In addition to analyzing GDP data and the role of public spending policies in promoting themFindings: The results lead to knowing the role played by public spending in the GDP during the research period, as the researcher tries to reach a statement of the result of the direct relationship between public spending policies and GDP.Research Implications: The results emphasize the increasing importance of integrating the current research variables in the formulation of expenditure policies that suit the Iraqi economy in line with strengthening the GDP in the future by directing spending to the productive sectors, which leads to increasing their contribution to the GDP.Originality/Value: This study works to enhance awareness of the importance of directing public spending efficiently and effectively to ensure the achievement of its future goals, the most important of which is to enhance the gross domestic product.